Low Back Pain And Work Related Factors Among Nurses In Intensive Care Units - Khan, Areeba Yaqoob; Saif, Anisa (Biological and Clinical Sciences Research Journal, 2025)
Low back pain (LBP) is a common occupational health concern among nurses, particularly those working in intensive care units (ICUs), due to the physical demands and shift patterns associated with patient care. Objective: To assess the prevalence and identify risk factors associated with low back pain among ICU nurses at a tertiary care hospital. Methods: A descriptive cross-sectional study was conducted from January 2024 to January 2025 at the Intensive Care Unit of Chaudhary Pervaiz Elahi Institute of Cardiology, Multan. A total of 100 ICU nurses directly involved in patient care were included. LBP prevalence was assessed based on self-reported pain frequency over the last 12 months using a four-point Likert scale: always, once weekly, once monthly, once bimonthly, or several months. Nurses also reported whether they had sought medical treatment for LBP. Odds ratios (OR) were calculated to determine the risk associated with clinical specialities, night shift frequency, and perception of staffing adequacy. Results:88% of ICU nurses reported experiencing low back pain in the past year. Pain was reported as occurring once a week by 40%, once a month by 28%, and always by 20% of participants. Only 20% of nurses had sought medical consultation for their symptoms. Nurses working in general surgical ICUs had a significantly elevated risk of LBP (OR: 1.71, 95% CI: 0.98–2.83, p=0.049), while those in cardiology and neurology ICUs were at the highest risk (OR: 3.01, 95% CI: 1.26–5.49, p=0.009). Additionally, working ≥6 night shifts per month increased LBP risk by 50%, and nurses perceiving inadequate staffing had a 65% higher risk of LBP. Conclusion: There is a high prevalence of low back pain among ICU nurses, with significant associations with clinical speciality, night shift frequency, and perceived staffing levels. Targeted interventions, including ergonomic training, workload redistribution, and optimised staffing, are needed to mitigate the burden of LBP in ICU settings.